Development of dwarf B. carinata genotype employing inter-specific hybridization between B. juncea and B. carinata and cyto-morphological studies for patterns of variation - Arun Kumar; HS Meena; Bhagirath Ram; Priyamedha; VV Singh; PK Rai (Journal of Oilseed Brassica, 2026)
Successful inter-speciûc hybrid plants were obtained through sexual hybridization between Brassica juncea cv. NRCDR-2 (2n=4x=36, AABB), and B. carinata, NRCKR-304 (2n=4x=34, BBCC) using the latter as a pollen parent. Morphologicaland cytological analyses were carried out to conûrm the hybrid nature of F1 plants. The F1 plants (2n=35) were intermediatefor most of the morphological attributes. Although, the F1s showed poor pollen fertility, nevertheless, few seeds wereobtained from open pollination. Meiotic analysis of F1 plants showed a predominance of univalents, a typical feature ofwide hybrids. The occurrence of chromosome association ranging from bivalents (0–16), trivalent (0–1) and quadrivalent(0–1) in the F1s indicated homeologous pairing between the AB and BC genomes. The study suggests that B. carinatahas partial genome homeology with B. juncea. Patterns of variations in F2 progenies of the cross were estimated. In theF2 generation, more number of plants resembling B. juncea was observed indicating transgressive segregation. Presentstudy also indicated that inter-speciûc hybridization in Brassica could be a potential source for generating variabilitybesides broadening the genetic base and segregants with desirable agro-economical characteristics were selected forfurther advancement and evaluation.